Does the Use of Social Media Tools in Classrooms Increase Student Commitment to Corporate Social Responsibility? - Rodríguez-Gómez, Sara; Garde-Sánchez, Raquel; Arco-Castro, María Lourdes; López-Pérez, María Victoria (Frontiers in Psychology, 2020)
There is an increasing demand for ethical and Corporate Social Responsibility (CSR) practices by companies. This competence has to be introduced in students’ training in business degree programs, and a check must then be done to determine if the students have come to appreciate the importance of CSR commitments. Using the framework of Stakeholders Theory, this work aims to examine students’ perceptions of ethical and CSR practices and commitment to different stakeholders, as well as the factors that lead students to act in a socially responsible way. Furthermore, we hope to identify how the perception of CSR can be improved when Web 2.0 and social media tools that have proven effective in transmitting emotions and values are used in classrooms to teach these ideas. To this end, a survey was carried out in the year 2019 with 1,030 first-year students; it was administered at the beginning of the semester and also at the end of the semester after the training activities had been carried out. The main finding of the research is that students start with the belief that ethics and CSR are developed for reasons of image and legitimacy; however, after receiving training on these topics through tools that take into account emotions and values, they start to value the importance of the company as an agent of social change. The main practical and managerial implication is that methods based on Web 2.0 and social media tools are useful to teach ethics and CSR; the theoretical contribution is that students take into account the welfare of others. This finding contributes to Stakeholder Theory in a higher education context.